PEMANFAATAN PUPUK ORGANIK CAIR KULIT BAWANG MERAH PADA TANAMAN TERONG UNGU (Solanum melongena L). - Sinu, Grasiana Tryfonia Dehot; Agastya, I Made Indra; Anggarbeni, Susilo Ribut; Indawan, Edyson; Hapsari, Ricky Indri (Universitas Tribhuwana Tunggadewi, 2024)
This research aims to determine the use of shallot skin liquid organic fertilizers on the growth of eggplant plants and determine the application of different doses to eggplant plants. The method used in this research used a factorial Randomized Block Design (RAK) with two factors where the first factor was eggplant variety M1: Mustang F1, M2 : LagunaF1, and the second factor was the dose of Liquid Organic Fertilizer (POC) shallot skin V0 : no POC shallot skins, V1 : 20 ml/L POC of shallot skins, V2 : 40 ml/L POC of shallot skins, V3 : 60 ml/L POC of shallot skins, V4 = 80 ml/L POC of shallot skins. The results showed that shallots skin POC on both varieties did not provide significant interaction. Shallots skin POC independently affected plant height and number of leaves, with the highest results in the V4 treatment with an average of 26.00 cm and 21.84 strands. While in the parameters of the result, the V4 treatment showed the highest results in fruit weight, namely 243.99 g. Onion skin POC can increase eggplant plant growth with the highest dose of 80 ml/L..